DESAIN DAN IMPLEMENTASI GAME PETUALANGAN KURT PADA MOBILE PHONE MENGGUNAKAN J2ME - Sundari, Retno; Arianto, Sofi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
Advances in communications technology is growing very rapidly, especially mobile communication technology. In addition to the hardware technology continues to evolve, technology software applications are also progressing very rapidly. One form of the advancement of mobile communication technology and the growing popular today are Java-based applications on mobile phones using J2ME (Java 2 Micro Edition).The purpose of this thesis is to design and implement an application program on mobile games using J2ME, so it can apply the application that is the result of a game development on mobile phones so that the resulting game interesting. Software (software) Kurt adventure computer game was created using the programming language Java 2 Micro Edition (J2ME).Â Keywords: Design and Implementation, Games, Mobile Phone, J2ME